2019
DOI: 10.1038/s41419-018-1279-1
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oncogenic action of LOX-1 and its splice variant LOX-1Δ4 in breast cancer phenotypes

Abstract: The identification of new predictive biomarkers and therapeutic target for tailored therapy in breast cancer onset and progression is an interesting challenge. OLR-1 gene encodes the cell membrane receptor LOX-1 (lectin-like oxidized low-density lipoprotein receptor). We have recently identified a novel alternative OLR-1 isoform, LOX-1Δ4, whose expression and functions are still not clarified. In the present paper, we demonstrated that LOX-1 is overexpressed in 70% of human breast cancer (n = 47) and positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Several studies have indicated that overexpression of COX-2, and to a lesser extent of COX-1, is directly associated with breast cancer [24][25][26]. Similar to COXs, lipoxygenase (LOX), which produces prostaglandins via a different pathway, has been found to be associated with breast cancer [27][28][29]. Taken together, overexpression of COXs and LOXs has been directly associated with breast cancer, which supports our results that mastitis increases the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have indicated that overexpression of COX-2, and to a lesser extent of COX-1, is directly associated with breast cancer [24][25][26]. Similar to COXs, lipoxygenase (LOX), which produces prostaglandins via a different pathway, has been found to be associated with breast cancer [27][28][29]. Taken together, overexpression of COXs and LOXs has been directly associated with breast cancer, which supports our results that mastitis increases the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…LOX-1, a marker for atherosclerosis (2), results to be overexpressed in several types of cancer, suggesting its role at the interface of atherosclerosis, metabolic disease and cancer (3, 4, 68, 33).…”
Section: Discussionmentioning
confidence: 99%
“…OxLDL lecithin-like receptor 1 (OLR1) is the main receptor for internalization of oxLDL. It is overexpressed in human breast cancer and positively correlates to tumor stage and grade [80]. A microarray analysis of hearts of Olr1 KO mice compared with wild-type mice showed a reduction in the expression of nuclear factor κB (NF-κB) target genes involved in cellular transformation (regulation of apoptosis, proliferation, wound healing, defense response, immune response, and cell migration) as well as an inhibition of key enzymes involved in lipogenesis.…”
Section: Low-density Lipoprotein and Breast Cancermentioning
confidence: 99%